The Conduct of War : A Short Treatise on its Most Important Branches and Guiding Rules - Goltz, Colmar, Freiherr Von Der; Edited by Capt. Walter H. James (London Kegan Pual, Trench, Trubner & Co. Ltd., 1899)
This book is a treatise on the guiding rules of war according to Lt. General Colmar von der Goltz of the Prussian Army.
Translated by Major G. F. Leverson, P.S.C., Roy. Eng.
Keywords: Military art and science -- War